Un cadre conceptuel pour explorer localement les facteurs de vulnérabilité et les options d’adaptation aux changements climatiques - Nathalie Beaulieu; Julia Santos Silva; Steve Plante (VertigO)
This article describes a conceptual framework in order to explore drivers of vulnerability to climate-related hazards as well as options to adapt to climate change. The framework helps to guide reflections in a simple and non-technical language while being compatible with different conceptualisations of vulnerability. Il was developed through the elaboration of an action plan for adaptation with the municipal administration of Rivière-au-Tonnerre on the northern coast of the Gulf of Saint Lawrence, in the province of Québec in Canada, in collaboration with the planning department of the regional municipality (MRC) of Minganie. The framework consists in separating the causal chain for the development of consequences from climate-related hazards into three phases : The development of secondary hazards in the natural environment ; biophysical damages ; and the disturbance of human activities. It is implemented through two tables guiding a) factors favouring negative consequences, therefore contributing to vulnerability and risk, and b) factors and practices reducing negative consequences, contributing to resilience. The latter table allows exploring practices that can be improved or new actions to implement, pointing to opportunities for adaptation. The example developed in Rivière-au-Tonnerre helped situating the role of different actors at the local, regional, provincial and federal levels. It also allowed indentifying factors that could be quantified to monitor the effects of certain adaptation initiatives.